Detection of Ganglion Cell Loss in Preperimetric Glaucoma by Fourier-Domain Optical Coherence Tomography - Dubey, Suneeta; Prasanth, Baswati; Chauhan, Lokesh; Mukherjee, Saptarshi (International Journal of Clinical and Experimental Ophthalmology, 2017)
Background: Glaucoma is a multi-factorial optic neuropathy characterized by a loss of retinal ganglion cells with subsequent loss of the retinal nerve fibers ultimately resulting in visual impairment. The macula region has a high density of retinal ganglion cells thereby being a likely region to detect early cell loss .Since glaucoma affects mainly the inner layers of the retina, Ganglion Cell Complex (GCC) mapping can help to detect glaucomatous damage early as compared to the total retinal thickness. Purpose: To map GCC thickness and average Macular Retinal (MR) thickness with high-speed Fourier-Domain Optical Coherence Tomography (FD-OCT) and correlate it with the Retinal Nerve fiber layer (RNFL) thickness in preperimetric glaucoma. Design: Observational cross-sectional study. Methods: Forty four eyes diagnosed as preperimetric glaucoma were studied. GCC, MR thickness and RNFL thickness was mapped using the RTVue FD-OCT system. The GCC thickness map, the deviation map and the significance map were obtained in all cases. Average GCC thickness and MR thickness were correlated with the RNFL thickness. Results: Average GCC of patients was 85.99±6.9 µm. There was GCC loss in 35 (87.5%) eyes which correlated well with areas of RNFL loss (r=0.408, p<0.001). Nine (22.5%) eyes were seen to have decreased MR thickness. GCC loss correlated well with the loss of average RNFL thickness and MR thickness. Further GCC loss was also seen in 23 (74.19 %) eyes with a normal MR thickness. Conclusion: GCC analysis may prove to be a robust diagnostic parameter and is complementary to RNFL analysis in preperimetric glaucoma.